DA'WAH STRATEGIES OF THE HALAL PRODUCT GUARANTEE AGENCY (BPJPH) IN PROMOTING HALAL CERTIFICATION FOR FOOD AND BEVERAGE PRODUCTS IN DAIRI REGENCY - Anggi Nanda Fadilah Nasution; Tengku Walisyah (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2026)
This study systematically investigates the da'wah (Islamic outreach) strategies implemented by the Halal Product Guarantee Agency (BPJPH) to promote halal certification of food and beverage commodities in Dairi Regency. This region was intentionally chosen for its distinctive demographic profile, marked by a Muslim minority, which introduces specific sociological and administrative challenges for religious outreach. Utilizing a robust qualitative methodology, this research triangulates empirical data collected through in-depth interviews, participatory observation, and comprehensive document analysis. The results reveal a collaborative framework in which BPJPH works closely with the Islamic Guidance Section of the Ministry of Religious Affairs and Halal Product Process Facilitators (P3H). These entities jointly implement multifaceted da'wah strategies that include formal regulatory policies, such as the mandatory halal certification directive, as well as community-based initiatives like sermons at local religious study circles, targeted Ramadan outreach programs, and focused interpersonal engagements. Furthermore, the integration of da'wah principles is accomplished by aligning the theological requirements of Sharia law with practical economic incentives for Micro, Small, and Medium Enterprises (MSMEs). Despite significant technical and spatial challenges, this comprehensive approach has demonstrated considerable effectiveness. It enhances regulatory literacy, increases consumer confidence in product integrity, and raises awareness among regional business operators about the commercial and ethical significance of obtaining formal halal accreditation.